2015
DOI: 10.1002/jpoc.21161
|View full text |Cite
|
Sign up to set email alerts
|

Using Participatory Video to Understand Diversity Among People With Dementia in Long‐Term Care

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…However, it is important not to disregard group-based LSW, as almost one-third of participants with dementia indicated that they would prefer this over the individual option. In previous research, positive outcomes of digital LSW have been identified in both individual and group settings among community (Massimi et al, 2008;Stenhouse et al, 2013), and care home residents (Damianakis et al, 2010;Ludwin & Capstick, 2015;Subramaniam & Woods, 2016). Similarly, a previous qualitative study found that participants in a digital LSW group felt the social aspect of the groups was the main benefit, while those in individual settings discussed the benefits of LSW itself, and couldn't see how it would be feasible in a group setting (O' Philbin et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, it is important not to disregard group-based LSW, as almost one-third of participants with dementia indicated that they would prefer this over the individual option. In previous research, positive outcomes of digital LSW have been identified in both individual and group settings among community (Massimi et al, 2008;Stenhouse et al, 2013), and care home residents (Damianakis et al, 2010;Ludwin & Capstick, 2015;Subramaniam & Woods, 2016). Similarly, a previous qualitative study found that participants in a digital LSW group felt the social aspect of the groups was the main benefit, while those in individual settings discussed the benefits of LSW itself, and couldn't see how it would be feasible in a group setting (O' Philbin et al, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…Some small studies have found promising evidence that digital LSW can benefit people with dementia in the areas of communication, self-identity, quality of life, mood, and enjoyment (Damianakis, Crete-Nishihata, Smith, Baecker & Marziali, 2010;Ludwin & Capstick, 2015;Massimi et al, 2008;Stenhouse, Tait, Hardy, & Sumner, 2013;Subramaniam & Woods, 2010Subramaniam & Woods, 2016. LSW is typically carried out by 'front-line' health and social care staff, through services/organisations, or within the realms of research.…”
Section: Advancements In Information and Communication Technology (Icmentioning
confidence: 99%
“…This orientation is compatible with the use of novel, community-oriented research methods. Capstick (2011) and Ludwin & Capstick (2015) used participatory visual methods, as part of service user initiatives at the School of Health Studies, University of Bradford, UK. The method of filmmaking used in these studies is similar to our approach in its objective of encouraging people living with dementia to create their own stories about an aspect of their lives and thus empowering them in communicating their memories in an attractive digital format.…”
Section: The Our Story App and Personalised Multimedia Storiesmentioning
confidence: 99%
“…Findings on the formal measures used for the study (wellbeing, social participation and occupational diversity) were all positive (Ludwin and Capstick 2015). The present paper is based, however, on a secondary analysis of the content of the films themselves, and here we aim to enhance understanding of the historical significance of place in emotional memory for people with dementia by exploring in depth some of the 'patterned regularities' (Wolcott 1994) in participants' choice of subject matter for their films.…”
Section: Key Themesmentioning
confidence: 94%